PENATAAN HIRARKI PELABUHAN DI GUGUS PULAU DAERAH TERTINGGAL DI SULAWESI BAGIAN SELATAN DALAM KERANGKA SISTEM TRANSPORTASI NASIONAL - Ganding Sitepu (Jurnal Transportasi, 2008)
Abstract The islands located in an area of about 160.000 sq km in southern part of Sulawesi,  consist of 5 regencies. There are 5 big islands (more than 150 sq km each)  in this area. The economic level of these islands is still low and, therefor,  can not afford the commercial transportation tariff. Since 1974 the government of Indonesia has provided so called pioneer shipping (subsidized financially by government) in order to improve accessibility of these islands. So far, the economic level of population of these islands has not much improved. The pioneer ships are general cargo type (coaster), with long distance trips (average 1.660 sea mile) and take about 18 days for a round trip. The determination of shipping routes for servicing less developed islands are made without any deep analysis. This paper began with analysis of selecting ports in order to improve routes of the pioneer ships. To determiny an optimum sea transportation services into the area, the shipping should be classified in regional pioneer routes (main regional feeder), secondary regional feeder, and people shipping. This study found out that the total 22 ports in the area can be divided to 3 categories (hierarchy), 2 regional ports, 7 regional main ports, and 8 secondary regional feeder ports, and 5 people shipping ports.  Keywords: port hierarchy, pioneer shipping, remote islands.